FRI0563 Detection of IGG Anti-Domain I Beta2 Glycoprotein I Antibodies by Chemiluminescence Immunoassay in Primary Antiphospholipid Syndrome. (9th June 2015) - Meneghel, L.; Ruffatti, A.; Gavasso, S.; Tonello, M.; Mattia, E.; Spiezia, L.; Tormene, D.; Hoxha, A.; Fedrigo, M.; Simioni, P.
Abstract : Background: IgG anti-Domain I (anti-DI) β2 Glycoprotein I (β2GPI) antibodies are the main subset of anti-β2GPI antibodies and are associated to thrombotic risk in antiphospholipid syndrome (APS), but their detection is technically difficult because the Domain I (DI) epitope is exposed only upon a conformational change in β2GPI molecule. Chemiluminescence immunoassay (CLIA), a new fully-automated technology which exploits a light-emitting chemical reaction for antibody detection, has become available for testing anticardiolipin (aCL) and anti-β2GPI antibodies and, recently, also anti-DI antibodies. Objectives: The aim of this study was to assess the clinical value of IgG anti-DI antibodies in a large homogeneous cohort of primary APS patients and in a group of ELISA-negative patients with clinical manifestations of APS. Methods: The study population included 88 patients with PAPS, 63 ELISA-negative subjects and 96 controls. IgG anti-DI, IgG anticardiolipin (aCL), IgG anti-β2GPI antibodies were assayed using CLIA (HemosIL AcuStar®). Lupus Anticoagulant (LA) was assessed according to the updates international guidelines [1]. Results: The sensitivity and specificity of IgG anti-DI antibodies were comparable to those of IgG aCL and IgG anti-β2GPI antibodies, while IgG anti-DI antibody sensitivity was significantly higher than that of LA (Table 1 ). There was a significant agreement and association (p<0.001 for both) and a significant titre correlation (p<0.001) between IgG anti-DI and IgG aCL as well as IgG anti-β2GPI antibodies (Table 2 ). IgG anti-DI antibody prevalence and mean titres were significantly higher in the thrombotic than in the pregnancy morbidity PAPS patients (79.6% vs 23.5% and 823.9 CU vs 34.0 CU, p<0.001 for both). Among the conventional aPL antibody profiles, the frequency of IgG anti-DI antibodies and their titres were significantly higher in the triple positivity group (94.1%, 1162.5 CU) compared to single (15.0%, 4.1 CU) and double positivity (47.1%, 443.8 CU) ones (p<0.001 for both). Finally, the prevalence of IgG anti-DI antibodies detected by the CLIA method was not significantly different in the ELISA-negative patients compared to that found in the controls (6.3% vs 3.7%, p=0.47). Conclusions: This study provides further evidence that anti-DI antibodies can be considered a promising biomarker for both APS classification and risk assessment particularly in patients suffering from vascular thrombosis. References: Pengo V, Tripodi A, Reber G, Rand JH, Ortel TL, Galli M et al. Update of the guidelines for lupus anticoagulant detection. Subcommittee on Lupus Anticoagulant/Antiphospholipid Antibody of the Scientific and Standardisation Committee of the International Society on Thrombosis and Haemostasis. J Thromb Haemost 2009;7:1737-40. Disclosure of Interest: None declared